MITIGATING EFFECTS OF VOLTAGE DEVIATION ON DELSUTH HEALTH CARE FACILITY UTILIZING DYNAMIC VOLTAGE RESTORER (DVR) - UMUKORO ARIEYERI PATRICK; PATRICK OSHEVIRE (Journal of Engineering Studies and Research)
This paper examined power supply at DELSUTH with the aim of mitigating effects of voltage deviation. The 11KV feeder from 7.5MVA substation which supplies the Hospital was analyzed using Dynamic Voltage Restorer (DVR) device on ETAP 16.0 software environment. It was observed that load flow analysis is vital in understanding the operating nature of the network, by considering the reactive power, voltage deviation magnitude and power losses in the network. From the simulation there was low voltage profile in the transformers feeding the clinical area. The voltage profile was improved by upgrading the network to standard power factor.